2022
DOI: 10.1186/s40360-022-00562-w
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the importance of mixing during preparation of antibiotic infusions

Abstract: Background The mixing step after medication addition to the infusion bag is frequently omitted during the preparation of drug infusions. However, the importance of mixing when preparing antibiotic infusions is still unknown. Methods The primary aim of this study was to assess the importance of the mixing step by comparing the concentrations of unmixed antibiotic infusions (cefuroxime, flucloxacillin, meropenem, and vancomycin) with the declared con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This error type was excluded because it was considered irrelevant because spontaneous mixing occurs during normal handling, especially with antibiotic admixtures (82% of the included admixtures). 23 , 24 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This error type was excluded because it was considered irrelevant because spontaneous mixing occurs during normal handling, especially with antibiotic admixtures (82% of the included admixtures). 23 , 24 …”
Section: Methodsmentioning
confidence: 99%
“…The error type incomplete mixing (i.e., container inverted less than 3 times or not shaken) occurred in the vast majority of admixture preparations (n = 1334; 82.0%). This error type was excluded because it was considered irrelevant because spontaneous mixing occurs during normal handling, especially with antibiotic admixtures (82% of the included admixtures) 23,24 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors identified an error in the authors’ list.…”
mentioning
confidence: 99%